2007
DOI: 10.1002/jnr.21386
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic properties of the redox switch/redox coupling mechanism as determined in primary cultures of cortical neurons and astrocytes from rat brain

Abstract: We investigate the mechanisms underlying the redox switch/redox coupling hypothesis by characterizing the competitive consumption of glucose or lactate and the kinetics of pyruvate production in primary cultures of cortical neurons and astrocytes from rat brain. Glucose consumption was determined in neuronal cultures incubated in Krebs ringer bicarbonate buffer (KRB) containing 0.25-5 mM glucose, in the presence and absence of 5 mM lactate as an alternative substrate. Lactate consumption was measured in neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
1
24
0
1
Order By: Relevance
“…The removal of glucose from the Ringer’s in the substitution experiment reduces the substrate availability for glycolysis in both neurons and astrocytes. Furthermore, in both the replacement and supplementation experiments, the increased lactate in the bath will inhibit glycolysis while providing lactate for use in the TCA cycle [63]. Therefore, these findings demonstrate that the vast majority of the onbeam light phase is due to oxidative metabolism and that neurons can sustain oxidative metabolism using lactate, which is in agreement with the ANLS hypothesis [16, 24, 56, 6467].…”
Section: Discussionsupporting
confidence: 65%
“…The removal of glucose from the Ringer’s in the substitution experiment reduces the substrate availability for glycolysis in both neurons and astrocytes. Furthermore, in both the replacement and supplementation experiments, the increased lactate in the bath will inhibit glycolysis while providing lactate for use in the TCA cycle [63]. Therefore, these findings demonstrate that the vast majority of the onbeam light phase is due to oxidative metabolism and that neurons can sustain oxidative metabolism using lactate, which is in agreement with the ANLS hypothesis [16, 24, 56, 6467].…”
Section: Discussionsupporting
confidence: 65%
“…In turn, any effects of changes of lactate on the NADH/NAD + ratio in one place lead to similar effects in widely distributed populations of cells (cf. Cerdán et al, 2006; Ramírez et al, 2007; Rodrigues et al, 2009). In fact, the transfer of lactate is so efficient that it is difficult to observe any differences of lactate concentrations across cell membranes in brain tissue (Gjedde and Marrett, 2001; Ido et al, 2001, 2004; Gjedde et al, 2002), such that significant cellular compartmentation of lactate is unlikely to exist under normal conditions, except briefly.…”
Section: Near-equilibrium Reactions and Lack Of Compartmentationmentioning
confidence: 99%
“…Different experimental procedures in preparing the cell cultures might explain the different outcomes of the afore mentioned in vitro studies (Bak et al , 2006; Bouzier-Sore et al , 2006; Ramirez et al , 2007). From a more general perspective, a key component about cellular function that should be kept in mind is that electrical excitability is compromised under in vitro conditions because cell membranes are in an unusual environment.…”
Section: A Energy Metabolism Of Neuronal Activation: the Available Hmentioning
confidence: 99%
“…Results by Ramirez et al (2007) suggested that ∼3.6 mM extra-cellular [Lac] is needed to inhibit neuronal glucose consumption by 50%. However, tissue [Lac] has been measured to increase no more than 1 μmol/g during stimulation (Dienel et al , 2002; Frahm et al , 1996; Madsen et al , 1999; Mangia et al , 2007a; 2007b; Prichard et al , 1991); even the increases in [Lac] measured in the extra-cellular medium did not overcome this limit (Hu and Wilson, 1997).…”
Section: B Interpretation Of Experimental Findings Obtained With In mentioning
confidence: 99%